Effects of rapid weight loss on body fluids and aerobic performance among combat athletes - Feist, J.; Reljic, D.; Jost, J.; Kieser, M.; Friedmann-Bette, B. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Purpose: It was recently shown that rapid weight loss (RWL), which is practiced by many combat athletes before competition, is nearly exclusively achieved by a loss of body water resulting in hypohydration (Reljic et al., 2013).The purpose of this study was to test the hypothesis that the hypohydration impairs aerobic performance. Methods: During a normal training period (t-1), ~1-2 days before competition (t-2) and 1 week after competition (t-3), data was collected from 14 athletes (weight loss group, WLG; 22.6±4.0 y; 176±8 cm; 77.0±12.9 kg) who reduced their body weight (BW) before competition within a few days by individual methods and from 14 subjects who did not reduce BW (control group, CG; 23.8±4.8 y; 178±8 cm; 78.3±11.6 kg). Total body water (TBW), intra- (ICW) and extracellular water (ECW) were estimated by bioelectrical impedance analysis and urine specific gravity (USG) was determined. Thereafter, a step-wise graded treadmill-test was performed to determine performance at 4-mmol- (4LT) and individual (ILT, basic lactate +1.5 mmol) lactate thresholds as well as peak-performance and VO2peak. Results: In WLG, a BW reduction by 5.5±0.9% led to significant losses in TBW (6.5±2.9%, p<0.001), ECW (4.8±2.3%, p<0.001) and ICW (4.8±2.3%, p<0.001). At t-3, body fluids had returned to baseline levels. USG had increased from 1020±8 (t-1) to 1026±7 (t-2) and had decreased again to 1021±7 at t-3. In CG, no significant changes ocurred. In WLG, peak performance (15.9±1.5 km/h) and VO2peak (4.2±0.7 L) had decreased at t-2, but were not statistically different compared to t-1 (16.2±1.3 km/h, 4.4±0.6 L) and t-3 (16.2±1.6 km/h, 4.3±0.7 L). Relative VO2peak did not change significantly. Peak lactate values (p<0.01) and respiratory exchange ratios (RER) (p<0.001) decreased significantly from t-1 to t-2 (10.9±2.2 to 9.3±2.2 mmol/L; 1.16±0.08 to 1.07±0.07) and almost returned to baseline values at t-3. 4LT-running speed at t-2 (3.81±0.35 m/s) was higher compared to t-1 (3.65±0.34 m/s, p<0.01). Speed at ILT did not change significantly. In CG, no significant changes occurred in VO2peak, peak-, 4LT- or ILT-performance. Conclusion: The ~6% hypohydration after RWL did not significantly affect peak performance and speed at the ILT. However, the significant decrease in peak lactate and peak RER as well as the increased speed at 4LT suggest glycogen depletion.